English Teachers’ Perception on Assessment Changes in The Merdeka Curriculum at SMAN 7 Padang - Tsalsabilla, Aderany Raulia; Oktavia, Witri (Journal of English Language Teaching, 2024)
These researchers are interested in conducting research aims to reveal the perceptions of English teachers at SMAN 7 Padang regarding changes in assessment that have occurred in the Merdeka curriculum. This research uses mixed methods to collect, analyze, and integrate quantitative and qualitative data in one study. From the analysis data, it is concluded that English teachers have a positive perception of assessment changes in the Merdeka curriculum. The results of the research show that assessments in the Merdeka curriculum, namely diagnostic assessment, formative assessment, and summative assessment are effective assessments to help teachers recognize, monitor, and measure students' abilities and understanding of the material so that teachers can identify and evaluate difficulties that arise faced by each student. This is because the implementation of the three assessments in the Merdeka curriculum is by their respective functions, such as the diagnostic assessment given by the teacher at the beginning of each semester, the formative assessment given by the teacher on each learning topic, and the summative assessment given by the teacher. given by the teacher at the end of each semester. Even though there are many benefits, teachers still experience several obstacles such as computers / PCs that still need to be provided and a stable internet network to access materials and lesson questions, this must be overcome with government assistance.